Peningkatan Kemampuan Berbicara Mata Pelajaran Bahasa Indonesia Melalui Model Pembelajaran Kooperatif Tipe Examples Non Examples - Ahmad Ibrohim; Siti Aminah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
The examples non examples learning model is a learning model that uses examples of pictures, symbols shown by the teacher through cases or pictures that are relevant to basic competencies. the use of cooperative learning models of the Examples non Examples type in class II students of MI Al Ma'arif Pesucen is expected to improve speaking skills. This study uses Classroom Action Research (CAR), which consists of two cycles. The quantitative approach in this study is based on the use of data, variables, operationalities, hypotheses, statistically significant. The data source for this research is from the research subjects themselves, namely students, through observations of fellow teachers, reflections from researchers and from test results. The subjects of this study were 25 students of grade II MI Al Ma'arif Pesucen. The results showed that the cooperative learning model of the examples non examples type could improve the speaking skills of class II MI Al Ma'arif Pesucen students. This is evidenced by the courage indicator from 64.57% in pre-cycle increased to 72.57% in cycle II, the description according to the picture from 75.20% increased to 91.20% in cycle II and the use of language from 75.50% in pre-cycle increased to 88.00% in cycle II.